2002
DOI: 10.1023/a:1015242627321
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: This review represents the first effort ever to survey the entire literature on auxin (indole-3-acetic acid, IAA) action in all plants, with special emphasis on the green plant lineage, including charophytes (the green alga group closest to the land plants), bryophytes (the most basal land plants), pteridophytes (vascular non-seed plants), and seed plants. What emerges from this survey is the surprising perspective that the physiological mechanisms for regulating IAA levels and many IAA-mediated responses foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
1
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 162 publications
(37 citation statements)
references
References 134 publications
1
31
1
1
Order By: Relevance
“…To fully elucidate and understand the reason(s) for and regulation of this spatio-temporal patterning would require detailed examinations of this process in all groups of land plants, and possibly in their ancestors as well. Of particular interest would be to trace the origin and evolution of auxin-regulated phyllotaxis formation from the angiosperms back through the ancestral lineages, as auxin appears to be a factor common to all land plants [138,139].…”
Section: Regulation Of the Phyllotactic Pattern Formation -Similaritimentioning
confidence: 99%
“…To fully elucidate and understand the reason(s) for and regulation of this spatio-temporal patterning would require detailed examinations of this process in all groups of land plants, and possibly in their ancestors as well. Of particular interest would be to trace the origin and evolution of auxin-regulated phyllotaxis formation from the angiosperms back through the ancestral lineages, as auxin appears to be a factor common to all land plants [138,139].…”
Section: Regulation Of the Phyllotactic Pattern Formation -Similaritimentioning
confidence: 99%
“…Alterations in auxin transport are associated with morphological differences both within (Bennett et al 2006) and between (Barkoulas et al 2008) species, and auxin has also been shown to underpin morphological convergence in leaf and rooting (Pires et al 2013) functions. Many developmental roles of auxin transport are conserved across land plants (Cooke et al 2002; Sanders and Langdale 2013), and disruption of transport can disrupt the development of major organ systems (Galweiler et al 1998). These data suggest a strong potential contribution of auxin transport to morphological change in plant evolution.…”
Section: Introductionmentioning
confidence: 99%
“…Endogenous IAA has been detected in cyanobacteria (Sergeeva et al , 2002; Hussain et al , 2010; Mazhar et al , 2013) as well as in brown algae (Le Bail et al , 2010), red algae (Ashen et al , 1999; Yokoya et al , 2010) and green algae (Mazur et al , 2001; Cooke et al , 2002; Stirk et al , 2013). Likewise, other auxin precursors and metabolites represented by tryptophan, anthranilate, IAM, indole-3-ethanol and IAOx were reported in substantial amounts in algae (Yokoya et al , 2010; Stirk et al , 2013, 2014), while in some cyanobacteria the species IBA was found as a predominant metabolite (Hashtroudi et al , 2013).…”
Section: Introductionmentioning
confidence: 99%